Diversidade de fungos basidiomicetos macroscópicos em áreas de reflorestamento de Eucalyptus spp. - Manzato, Beatriz Lourenço (2018)
Eucalyptus (Eucalyptus spp.) Is the forest genus most commonly used for commercial purposes worldwide. One of the biggest concerns of foresters is the waste left in the area after cutting the eucalyptus. In an attempt to solve the problem, producers end up opting for the method of lowering or removing the stumps. However, mechanized clearing causes numerous negative impacts to forest sustainability, among them, soil compaction, disturbance of the existing microbiota, removal of organic matter, impacts on carbon storage and emission of greenhouse gases, increase in erosion and alteration of nutrient cycling, as well as biodiversity reduction. The use of wood-degrading fungi can be an effective alternative for the removal of stumps, without negatively impacting the environment, but it is still a method little studied and used in areas of eucalyptus reforestation. This work is notable for the survey of the diversity of macroscopic basidiomycete fungi on stumps and eucalyptus litter, in reforestation areas in the interior of the State of São Paulo, of different ages (post-harvest stumps and one and two years after harvesting), with potential for use in organic production. Sixteen collections were carried out between September 2016 and August 2017, where each fungus collected was photographed individually for presumptive morphological identification. The collected fungi were isolated and preserved in the Department of Plant Protection of the "Júlio de Mesquita Filho" State University, Botucatu-SP campus. The most frequent fungi in the two - year - old stumps were of the genus Coprinus spp. and Ganoderma spp. In the area with one year old stumps, there was predominance of the genus Coprinus spp. and Galerina spp. No fungi were found on the stumps of the freshly cut area. There was a greater occurrence and diversity of macroscopic basidiomycete fungi in the area of reforestation of eucalyptus with two year old stumps.